Tin-doped perovskite mixed conducting membrane for efficient air separation - Zhang, Z.; Chen, Y.; Tade, Moses; Hao, Y.; Liu, Shaomin; Shao, Zongping (R S C Publications, 2014)
In this study, we propose a new tin-doped perovskite oxide, BaCo0.7Fe0.2Sn0.1O3-δ (BCFSn0.1), as a promising alternative material for a ceramic oxygen-permeating membrane. A high energy ball milling-assisted solid-state reaction method is used for the material synthesis. The effect of tin doping on the structure, electrical conductivity, oxygen activity, oxygen bulk diffusivity and surface exchange properties of the materials, sintering behaviour, and oxygen permeability of the related membranes is systematically investigated via transmission electron microscopy (TEM), environmental scanning electron microscopy (E-SEM), thermo-gravimetric analysis (TGA), oxygen temperature-programmed desorption (O2-TPD) and electrical conductivity relaxation (ECR), and oxygen permeation test. The minor substitution of B-site cations in BaCo0.7Fe0.3O3-δ (BCF) with tin is found to be highly effective in improving oxygen flux of the resultant membrane. Under an oxygen gradient created by air/helium, BCFSn0.1 membrane reaches fluxes of 9.62 x 10-7 and 3.55 X 10-7 mol m-2 s-1 Pa-1 [STP], respectively, at 900 and 700 °C, in sharp contrast with the flux values of 4.42 x 10-7 and 2.84 x 10-8 mol m-2 s-1 Pa-1 for BCF membrane with the same thickness of 1 mm. Favorable permeation stability is also demonstrated for the tin-doped membrane, and oxygen bulk diffusion is the main rate-limiting step for oxygen permeation, indicating a further increase in fluxes by reducing the membrane thickness.